2008
DOI: 10.1063/1.2830000
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electronic memory traps in the oxide-nitride-oxide structure of a polysilicon-oxide-nitride-oxide-semiconductor flash memory

Abstract: The origin of the electron memory trap in an oxide-nitride-oxide structure deposited on n-type Si is investigated by both capacitance-voltage and deep level transient spectroscopy (DLTS). Two electron traps are observed near 0.27 and 0.54eV, below the conduction band minimum of Si and are identified as the nitride bulk trap and the Si–SiO2 interfacial trap, respectively. The trap depth, viz., vertical distribution of the electron trap, in both nitride bulk and Si–SiO2 interface, are also estimated from the bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…These defects act like traps and influence the electrical transport and phototransport in these structures. 1,2,3,4,5,6,7,8,9,10,11,12,13,14,15 For instance, the dark current is reduced as the carrier concentrations decrease due to the trapping. This effect is compensated in the case of the phototransport by the decrease of the recombination rate if either the electrons or holes are trapped.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These defects act like traps and influence the electrical transport and phototransport in these structures. 1,2,3,4,5,6,7,8,9,10,11,12,13,14,15 For instance, the dark current is reduced as the carrier concentrations decrease due to the trapping. This effect is compensated in the case of the phototransport by the decrease of the recombination rate if either the electrons or holes are trapped.…”
Section: Introductionmentioning
confidence: 99%
“…23,24,25 Different methods were used to investigate these traps. The deep level transient spectroscopy (DLTS) method, 4,5,9,10,13,19,26 is the most used for the investigation of the deep traps. The method is based on the measurement of a transient junction capacitance and allows determining the energy of the trapping levels, as well as the concentration and capture cross-section of the trapping centers.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we examined the C-V hysteresis curve for SiO 2 and Cr-SrTiO 3 capacitors fabricated on Si substrates. 3,14 As a result, we found that the memory windows are 0 V for both samples, indicating that there is no charging effect in bulk or interfacial regions of the SiO 2 and Cr-SrTiO 3 layer. Therefore, the memory effect is believed to result from the nitride bulk and their interfacial layer.…”
Section: Resultsmentioning
confidence: 89%
“…1,2 However, significant challenges for the preservation of device endurance and retention of SONOS cells programmed and erased by direct tunneling is still a critical issue because of the thin tunnel oxide (Լ2.5 nm) needed for the tunneling of substrate electrons or holes. 3,4 Therefore, we tried to apply a resistance switching mechanism, known for its fast switching speeds (i.e., below 100 ns), to the SONOS structure in order to improve the memory performance. Consequently, a novel NAND flash concept using gate injection for the P/E operations has been developed in order to reduce the gate oxide degradation.…”
mentioning
confidence: 99%
“…In addition, we extrapolated ΔV FB against the read delay time to predict the long-term retention of the annealed samples A and B, and the values observed at 3 × 10 8 s (ten years) were 0.4 and 1.6 V, respectively, at room temperature. This result implies that the data retention in the two samples would be more than ten years at room temperature [26]- [28] in a P/E condition (±8 V at 1 ms). However, the data-retention time of sample B was longer than that of sample A.…”
Section: Resultsmentioning
confidence: 97%